2001
DOI: 10.1046/j.1365-2958.2001.02345.x
|View full text |Cite
|
Sign up to set email alerts
|

CspD, a novel DNA replication inhibitor induced during the stationary phase in Escherichia coli

Abstract: SummaryCspD is a stationary phase-induced, stress response protein in the CspA family of Escherichia coli. Here, we demonstrate that overproduction of CspD is lethal, with the cells displaying a morphology typical of cells with impaired DNA replication. CspD consists mainly of b-strands, and the purified protein exists exclusively as a dimer and binds to single-stranded (ss)DNA and RNA in a dose-dependent manner without apparent sequence specificity. CsdD effectively inhibits both the initiation and the elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 61 publications
2
99
0
12
Order By: Relevance
“…The proteins carrying substitutions of these amino acids with Arg fully retain their nucleic acid binding activity, but lose the ability to cause transcription antitermination and cold acclimation of cells as they lack the melting activity. 40,77 DNA microarray analysis of the cold shock response of the wild-type to cold-shock, stationary phase, nutrient starvation and freezing, 47,48 antibiotic biosynthesis, 49 UV sensitivity, 50 regulation of expression of proteins responding to osmotic stress, oxidative stress and stationary phase (UspA, OsmY, Dps, ProP and KatG 51 ), camphor resistance and chromosome condensation, 52,53 downregulation of λ Q-mediated transcription antitermination, 54 downregulation of poly(A)-mediated 3' to 5' exonucleolytic decay by PNPase, 55 inhibition of DNA replication, 56 and tolerance to solvents such as toluene. 57 The cold-shock induction of CspA and its homologs was studied in detail and was shown to occur at the levels of transcription, mRNA stability and translation.…”
mentioning
confidence: 99%
“…The proteins carrying substitutions of these amino acids with Arg fully retain their nucleic acid binding activity, but lose the ability to cause transcription antitermination and cold acclimation of cells as they lack the melting activity. 40,77 DNA microarray analysis of the cold shock response of the wild-type to cold-shock, stationary phase, nutrient starvation and freezing, 47,48 antibiotic biosynthesis, 49 UV sensitivity, 50 regulation of expression of proteins responding to osmotic stress, oxidative stress and stationary phase (UspA, OsmY, Dps, ProP and KatG 51 ), camphor resistance and chromosome condensation, 52,53 downregulation of λ Q-mediated transcription antitermination, 54 downregulation of poly(A)-mediated 3' to 5' exonucleolytic decay by PNPase, 55 inhibition of DNA replication, 56 and tolerance to solvents such as toluene. 57 The cold-shock induction of CspA and its homologs was studied in detail and was shown to occur at the levels of transcription, mRNA stability and translation.…”
mentioning
confidence: 99%
“…4, B and C). As expected, CspD, which has perfect alignment of the N terminus with CspB, has also been shown to form dimers (19). The genetic screen that implicated CspE in chromosome condensation also implicated CspC but no other Csps (32).…”
Section: Discussionmentioning
confidence: 72%
“…Dimerization of CspE-We determined the quaternary structure of CspE because two Csp proteins, CspB from B. subtilis and CspD from E. coli, have been shown to exist as dimers (19), and one, CspA from E. coli, exists as a monomer in solution (22,25). CspA contains 3 additional amino acids at the N terminus as compared with CspB, and it has been suggested that these 3 residues are responsible for the inability of CspA to dimerize.…”
Section: Cspe-ssdna Binding As Monitored By Gel Filtration-wementioning
confidence: 99%
See 2 more Smart Citations